1972
DOI: 10.1159/000230870
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Immunoglobulin Determinants and Antigen Receptors on the Surface of Rabbit Lymphoid Cells as Shown by Peroxidase-Labelled Antibody and Cell Rosetting Techniques

Abstract: (1) Lymphoid cells of rabbits have been rosetted by the mixed antiglobulin reaction and simultaneously stained for inimunoglobulin (Ig), using horse-radish peroxidase-labelled anti-IgG and prepared for electron-microscopic examination. The vast majority of rosetting cells (95%) were lymphocytes, and essentially all the lymphocytes which rosetted had membrane-staining for Ig. (2) Lymph-node cells from immunized rabbits rosetting via specific receptors with red cells carrying antigen were likewise stained for Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

1973
1973
1982
1982

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…The total percentage of Igbearing lymphocytes (type I and II com bined) in the lymph node population is 47%. This value is somewhat higher than those obtained by others using rabbit lymph node cells (12-32% [7]). However, using immunoperoxidase labeling for surface Ig on rat lymph node cells, Gonatas et al [8] determined that up to 46% of the lympho cytes had detectable surface Ig, and Ishii et al [9] using immunofluorescence found that 30% of the cells in rat lymph nodes had sur face Ig.…”
Section: Discussioncontrasting
confidence: 63%
“…The total percentage of Igbearing lymphocytes (type I and II com bined) in the lymph node population is 47%. This value is somewhat higher than those obtained by others using rabbit lymph node cells (12-32% [7]). However, using immunoperoxidase labeling for surface Ig on rat lymph node cells, Gonatas et al [8] determined that up to 46% of the lympho cytes had detectable surface Ig, and Ishii et al [9] using immunofluorescence found that 30% of the cells in rat lymph nodes had sur face Ig.…”
Section: Discussioncontrasting
confidence: 63%
“…The RFCs detected could, therefore, pos sibly be the cells involved in a delayed hypersensitivity response and thus presumably T cells. However, in a previous paper [8] it was shown that TNP-RFCs from animals skin-sensitized with DNFB have membrane Ig determinants detected by an antiglobulin reagent conjugated with horse radish peroxidase and examined in the electron microscope. There is con siderable evidence in species other than the rabbit that membrane Ig de terminants, as measured by this means, are surface markers for B cells, and only techniques of particularly high sensitivity can detect Ig determi nants on the surface of T cells [11].…”
Section: Discussionmentioning
confidence: 99%
“…The cell suspension was layered over a continuous Ficoll gradient (1.3-8%) as previously described [8] and centrifuged for 10 min at 90 g. A tenfold or better in crease in rosettes in the sediment resulted. This step was necessary to have a suffi cient number of TNP-RFCs in the EM preparation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct visual observations have been made using autoradi ography [Joneset al, 1970], supravital immunofluor escence [Pernis et al, 1970;Jones et al, 1973], indirect rosette formation [Coombs et al, 1970[Coombs et al, , 1977Wolf et al, 1971;Kent et al, 1972;Wilson et al, 1978] and immunoelectron microscopy Linthicum and Sell, 1974], However, because lymphocytes also have Fc receptors [Kerbel and Davies, 1974;Spiegelberg. 1974] it is not clear i f 'endogenous' or 'cytophilic' slg is being detected by these labeling techniques.…”
Section: Introductionmentioning
confidence: 99%